Vers une opérationnalisation de la notion de posture professionnelle en pédagogie universitaire - Nathalie Deschryver; Geneviève Lameul
In the field of university teaching and learning, in the contexts of change, innovation and particularly in that of the use of digital technologies which challenge the structures and organization of human action, teachers' "postures" are questioned increasingly frequently. But what hides behind this so little defined word : "posture" ? Where are the methodological tools that would allow to study it more precisely ? This article aims to explain a work initiated by the authors to answer both these questions and make some proposals in order to keep up with a research likely to lead to a conceptualization of this notion and its methodological documentation. Based on Lameul's definition, temporarily given in 2006, which highlights the components of the concept of "posture" (beliefs, intentions, actions), it sets out the possible use of Pratt & Associates' Teaching Perspectives Inventory (1998) to distinguish five "postural" tendencies. This work explains how - in the HY-SUP project - was made the choice rather to borrow Prosser and Trigwell's Approaches to Teaching Inventory tool (1999). After having studied the two instruments, this article shows their advantages and limitations of use. Assessing that these tools do not take into account everything that characterize our notion of "posture" (Lameul, 2006, 2016), it offers to complement it integrating specific questions issued from interviews with teachers (an illuminating input from mixed methods) to improve an instrumentation that would take better into account all the components of this complex concept of "posture".